Obstacles to global implementation of CAR T cell therapy in myeloma and lymphoma - Medina-Olivares, Fernando J.; Gómez-De León, Andrés; Ghosh, Nilanjan (Frontiers in Oncology, 2024)
Chimeric Antigen Receptor T-cell (CAR-T) therapies are transforming the treatment of B-cell lymphoproliferative disorders and multiple myeloma, yet global access challenges and barriers for their implementation persist. Global access disparities persist, particularly for persons living in low and middle-income countries and for underserved populations in high income countries. In this review we address patient-related factors including age, comorbidities, fitness, race and ethnicity, and geographic location for CAR-T access. Also, we review disease-related and health system barriers like disease biology, potential for short and long-term toxicity, insurance access, referrals, supply and manufacturing, regulation, costs and treatment center capacity. Lastly, alternatives for overcoming these barriers exemplified by research efforts worldwide are discussed, emphasizing the need for a multifaceted approach from all stakeholders to improve global accessibility and ensure equitable access and improved outcomes for patients worldwide.